Financial Knowledge as Youth Preneur Success Factor - Achmad Kautsar; Nadia Asandimitra (Journal of Social and Development Sciences, 2019)
Indonesia currently has developed entrepreneurship both conceptually and practically and has developed very rapidly. Knowledge that must be possessed by an entrepreneur is financial knowledge. Adequate financial knowledge is needed to provide entrepreneurial skills to make sound financial decisions. Other variables of financial behavior that are important to be measured along with financial knowledge on the success of young entrepreneurial business are the level of financial behavior and financial literacy. This research was designed as explanatory research to explain the subject of the influence of financial knowledge, financial literacy, and financial attitude towards young entrepreneurial success. The research was conducted in the city of Surabaya. The population of this study is young entrepreneurs who have micro businesses. The sampling technique is done in a way cluster sampling. The analytical method used in this study is to use multiple linear regressions with validity test, reliability test, classic assumption test, and hypothesis testing.